2021
DOI: 10.1155/2021/5510825
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of 2-Deoxy-2-[18F]fluoro-D-glucose Positron Emission Tomography/Computed Tomography after Autologous Hematopoietic Stem Cell Transplantation in Lymphoma Using Deauville Scores

Abstract: Purpose. In the present study, we mainly aimed to evaluate the prognostic value of 2-deoxy-2-[18F]fluoro-D-glucose ([18F]F-FDG) positron emission tomography (PET)/computed tomography (CT) after autologous stem cell transplantation (ASCT) in lymphoma. Procedures. A total of 76 lymphoma patients who benefited from [18F]F-FDG PET-CT (within 3 months and 3–6 months) after ASCT in our institution between April 2010 and December 2019 were enrolled in this retrospective study. These abovementioned patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…us, 18 F-FDG PET/CT is able to detect various body responses to this treatment during allogeneic hematopoietic stem cell transplantation treatment and facilitate further clinical treatment. Dai et al [32] used the improved 18 F-FDG PET/CT technique to evaluate the prognosis after stem cell transplantation, and found that the improved 18 F-FDG PET/ CT technique had a high application value in predicting PFS and OS in patients after stem cell transplantation treatment, especially in patients after 3 to 6 months of treatment. However, some experts proposed that for patients with relapsed or refractory T-lymphocytic lymphoma, 18 F-FDG PET/CT is used to predict the treatment prognosis after HSCT [33].…”
Section: Contrast Media and Molecular Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…us, 18 F-FDG PET/CT is able to detect various body responses to this treatment during allogeneic hematopoietic stem cell transplantation treatment and facilitate further clinical treatment. Dai et al [32] used the improved 18 F-FDG PET/CT technique to evaluate the prognosis after stem cell transplantation, and found that the improved 18 F-FDG PET/ CT technique had a high application value in predicting PFS and OS in patients after stem cell transplantation treatment, especially in patients after 3 to 6 months of treatment. However, some experts proposed that for patients with relapsed or refractory T-lymphocytic lymphoma, 18 F-FDG PET/CT is used to predict the treatment prognosis after HSCT [33].…”
Section: Contrast Media and Molecular Imagingmentioning
confidence: 99%
“…Reference [31] e sensitivity of FLT-PET/CT was lower than that of FDG-PET/CT e uptake of 18F-FDG in tumor tissue was higher than that of 18 F-FLT Reference [32] ASCT 18 F-FDG positivity after PET-CT was associated with lower PFS and OS; PET-CT outcome was the only independent factor associated with OS (p � 0.028); PET within 3-6 months after ASCT-In patients with CT scan, the PFS and OS prognosis were better in the PET-CT negative group 18 F-FDG PET/CT technology had high application value in predicting PFS and OS of patients after stem cell transplantation (especially the 3-6 months window period) Reference [33] PET/CT after HSCT (post-PET) was associated with PFS (P � 0.030). However, none of the assessed factors predicted OS.…”
Section: Research Conclusionmentioning
confidence: 99%
“…Moreover, 2-deoxy-2-[ 18 F]fluoro-D-glucose positron emission tomography/computed tomography ( 18 F-FDG PET-CT) has been widely used for staging, restaging, aggressiveness evaluation, and response monitoring of lymphoma since PET-CT was incorporated into the guidelines for lymphoma in 2007 [ 6 , 7 ]. Our preliminary studies [ 8 , 9 ] have shown that post-transplantation PET is helpful for the prognostic assessment of lymphoma patients.…”
Section: Introductionmentioning
confidence: 99%